Care Team Response to Patient Portal Message Content and Writing Style - Mitchell Tang; Lisa S. Rotenstein; Ariel D. Stern; Rebecca G. Mishuris; Michael L. Barnett (JAMA Network Open, 2026)
Importance Patient portal messages are an increasingly central channel for patient-clinician communication, but there are inequities in how responsive care teams are to messages sent by patients from historically marginalized groups. The reasons driving these disparities are not well understood. Objective To quantify factors that could potentially explain lower rates of care team response to messages sent by patients from historically marginalized groups. Design, Setting, and Participants This cross-sectional study used natural language processing to systematically extract message content and writing style features from portal message threads. Messages were from adult patients who sent a medical advice request message from January 1, 2021, to December 31, 2023, to a nontrainee physician, nurse practitioner, or physician assistant at a primary care practice. Data analysis was performed from May 2024 through June 2026. Exposure Message thread characteristics, including patient demographics, message content, and writing style. Main Outcomes and Measures Rates at which messages were responded to by care teams overall and by the message’s originally intended target clinician specifically. Regression analysis quantified the degree to which message content and writing style potentially explain differences in care team response across patient groups. Results The sample included 3 619 390 patient message threads sent by 511 020 patients. Of the threads, 4.0% were sent by Asian patients, 3.7% by Black patients, 5.9% by Hispanic patients, and 83.0% by White patients. Messages sent by patients from historically marginalized groups (eg, Black and Hispanic patients, patients with only a high school education, and Medicaid beneficiaries) received lower levels of care team response. Compared with White patients, Black patients had a 3.7–percentage point (pp) (95% CI, −4.1 to −3.3 pp; P < .001) lower response rate from the target clinician, representing an 11.6% reduction. Although message content was associated with target clinician response, it could not explain these differences. On the contrary, writing style accounted for 48.0% of the difference for Black patients, 34.9% for Hispanic patients, 60.5% for patients with only a high school education (relative to patients with a college degree), and 42.8% for Medicaid patients (relative to commercially insured patients). Conclusions and Relevance In this cross-sectional study of patient portal messages, writing style was a potential explanation for approximately half of the observed disparities in care team response, highlighting writing style as an important potential source of bias in message triage and a target for intervention.